Analysis of Prediction of Economic Losses due to Flood Disaster Hazards in Industrial Estates in Karawang Regency - Fathiyaturahma, Andina (TDMRC, Universitas Syiah Kuala, 2022)
Based on the National Disaster Management Agency, there was an increase in the total number of disasters from 2020 to 2022, which was initially 1,296 to 5402 disasters, with the highest percentage of disaster events being flood disasters with the highest frequency being in the West Java and DKI Jakarta areas (BNPB, 2022). The high frequency of floods that occur in the West Java region can certainly increase economic losses that are pretty high. On the other hand, West Java Province also contributes the third most significant national GDP. The sector that contributes the most to West Java's GRDP is the processing industry sector (BPS, 2017). Karawang Regency is one of West Java's destination areas for industrial development. In Karawang Regency, industrial areas are developing quite rapidly and are concentrated in the southern part of Karawang Regency (Telukjambe Barat, Telukjambe Timur, Ciampel, Pangkalan, Klari, and Cikampek districts). However, based on research conducted by the ITB Climate Change Center (2022), several points have a relatively high level of flood hazard in the area. That can bring considerable losses if the disaster occurs in an industrial area, so an analysis of losses due to flooding is needed at the location of the existing industrial site, which is currently in Karawang Regency. Therefore, this research was conducted to determine the condition of existing industrial land in flood-prone areas and to find predictions of economic losses that will be obtained in the event of a flood disaster on existing industrial land today. The research used secondary data in shapefiles (.shp) maps of Karawang Regency, planning documents, and related journals. Then, the analysis method that will be carried out is mapping disaster-prone areas in industrial estates and predicting economic losses due to flood disasters which will be carried out with a Geographic Information System (GIS). Based on the results of the analysis, it was found that 34.69% of the existing industrial land is located in flood-prone areas, which are predicted to impact the economic losses of IDR 65,049,705,681,272,-. That shows a need for a flood mitigation plan and the suitability of proper allocation of industrial estates to reduce the possibility of economic losses to be borne by the government.